The effect of cutting regime on economy properties of fodder sorghum Grazer N - Gordana Županac; Kristina Gršić; Mato Komesarović; Miljenko Konjačić; Darko Uher; Zvonimir Štafa (Mljekarstvo)
Sorghum hybrids fit well in the system of forage production on family farms. It can be sown after harvesting of winter and early sown spring crops, and utilized in few cuts during the second part of summer, until the beginning of autumn and appearance of the first frost. Furthermore, it can ensure good yields of quality green forage and the rest quantity can be ensilaged. In that way, higher yields of quality forage per hectare can be provided during vegetation season. The aim of this research, carried out in 2003 and 2004 at the Faculty of Agriculture in Zagreb, was to determine green matter yield, dry matter yield and forage quality of forage sorghum (hybrids Grazer N) at different development stages. The highest forage sorghum green mass (90,70 t ha-1) and dry matter yields (27,40 t ha-1) were obtained in panicles. The highest contents of crude proteins (13,35 %) were obtained at the forage sorghum height of 100 cm and significantly decreased until panicles. Crude fibres contents (31,20 %) significantly decreased until panicles.